ANALISIS PERSEPSI DAN PERILAKU MASYARAKAT TERHADAP KEBERADAAN KAWASAN KPHP MODEL POIGAR - Arif Irawan; Iwanuddin Iwanuddin; Jafred Elsjoni Halawane; Sulistya Ekawati (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
Implementation of community empowerment scheme in the Poigar Production Forest Management Unit (PFMU) Model area needs to take into account on community perception and behavior. This study aimed to determine the level of perception and behavior of the community towards the existence Poigar PFMU Model and to recommend the appropriate community empowerment scheme. To find out the perceptios and behavior of the Lolan Village community towards Poigar PFMU Model was by using Likert Scale. Furthermore, to determine the factors that influence people's behavior, then Spearman rank (Rs) correlation test was used. The results showed that the level of perception of Lolan village communities to the existence of the Poigar PFMU Model was in good category, while the society behavior was in the less category. A good public perception of the Poigar PFMU Model area, did not have significant influence on its behavior. Community social characteristics that correlate with the behavior of the community were among others: education, level of income sourced from outside the area and level of interaction with the forest. Based on this, community empowerment strategy that is most likely to do in Poigar PFMU Model is through the Forestry Partnership Scheme.